2017
DOI: 10.1088/1748-9326/aa81db
|View full text |Cite
|
Sign up to set email alerts
|

For wind turbines in complex terrain, the devil is in the detail

Abstract: The cost of energy produced by onshore wind turbines is among the lowest available; however, onshore wind turbines are often positioned in a complex terrain, where the wind resources and wind conditions are quite uncertain due to the surrounding topography and/or vegetation. In this study, we use a scale model in a three-dimensional wind-testing chamber to show how minor changes in the terrain can result in significant differences in the flow at turbine height. These differences affect not only the power perfo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
51
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 63 publications
(51 citation statements)
references
References 33 publications
0
51
0
Order By: Relevance
“…The resolution of the model and the ability to measure closer to the surface level thus appears to be one contributing factor. A separate study by Lange et al (2016b) recently submitted for publication investigates the effect of sharpening the escarpment edge. Preliminary analysis shows that this has a significant effect on the flow behaviour in the near-surface region.…”
Section: Effect Of Model and Measurement Resolution On The Turbulent mentioning
confidence: 99%
“…The resolution of the model and the ability to measure closer to the surface level thus appears to be one contributing factor. A separate study by Lange et al (2016b) recently submitted for publication investigates the effect of sharpening the escarpment edge. Preliminary analysis shows that this has a significant effect on the flow behaviour in the near-surface region.…”
Section: Effect Of Model and Measurement Resolution On The Turbulent mentioning
confidence: 99%
“…Recirculation occurs behind abrupt drops in terrain 2714 R. Menke et al: Characterization of flow recirculation zones elevation such as cliffs but also in the lee of gentle slopes of a certain steepness (Wood, 1995;Xu and Yi, 2013;Kutter et al, 2017). In addition, small terrain features (Lange et al, 2017) and the presence of forest canopy (Sogachev et al, 2004;Finnigan and Belcher, 2004) can modify the occurrence of recirculation drastically. Furthermore, the stratification of the atmosphere influences the occurrence of recirculation; for instance, recirculation was prevalent during neutral and unstable atmospheric conditions during the observational study of Kutter et al (2017).…”
Section: Introductionmentioning
confidence: 99%
“…Here, we investigate measurements from the Perdigão 2017 campaign where, in addition to sonic anemometers on 100 m high masts, pulsed Doppler lidars observed the flow over the two parallel ridges. To surpass the capabilities of point measurements from networks of masts, Doppler lidars have, not only in the Bolund campaign, proved capable of measuring flow phenomena such as wind turbine and wind farm wakes (Käsler et al, 2010;Iungo et al, 2013;Aitken et al, 2014;Menke et al, 2018a) and the effect of roughness changes on wind fields in different heights and nearshore flows (Mann et al, 2017). In addition to the advancements in the measurement technology, the orography of the Perdigão site can be approximated by two two-dimensional ridges as the Askervein's orography with a three-dimensional hill of about half the height of the Perdigão ridges.…”
Section: Introductionmentioning
confidence: 99%
“…Previous simplifications that ignored topography changes or reduced them to isolated features are often now not enough. For example, Lange et al [25] found minor changes in the terrain could have a significant effect on flow parameters for wind turbines and wind variables were sensitive to topography details.…”
Section: A Cfd Models Of Wind Flow Over Complex Terrainmentioning
confidence: 99%
“…Typical methods to do this may include scale wind tunnel testing, field experiments and numerical simulation [21], [25]- [27]. Each have associated issues such as scale, resources or limits to data being measured.…”
Section: A Cfd Models Of Wind Flow Over Complex Terrainmentioning
confidence: 99%